INSTITUTIONAL EFFECT ANALYSIS COMPARING ENERGY EFFICIENCY RETROFITTING FOR EXISTING RESIDENTIAL BUILDINGS PATTERNS IN CHINA - Zhao, Junna; Lou, Fanghong (European Scientific Journal, ESJ, 2013)
Buildings in China are important contributors to the country’s energy consumption and CO2 emissions. Energy use in building in northern heating regions of China accounts for more than 40% of secondary energy consumption in urban areas. The total building areas has increased 75% over the past decade. Approximately 2.5 billion m2 (nearly 1/3) of existing residential buildings in Northern China are worth retrofitting. Efficiency Retrofitting for Existing Residential Buildings (EERFERB) in China is undergoing a fast development support by both the Chinese Central Government and international governments and institutions. These international and domestic projects have not only played a significant role in enhancing China’s building energy efficiency, but also significantly promoted the quality of housing conditions for low- and middle- income populations. It is recognized that projects with government cooperation among countries and central-to-local government projects have different implementation patterns. These differences provide valuable lessons for selecting efficient project delivering institutions. This research will develop criteria to compare international government-to-government projects and domestic central government projects. Two typical projects in Beijing and Tangshan will be evaluated from the perspectives of regulatory support, organizations, retrofitting effects, financing mode, management structure, incentive and technical support, and community sustainability improvement. Based on it, both the strengths and weaknesses of both retrofitting delivery patterns are presented. Finally, lessons and experiences are extracted and the implications for instruction and decision-making for the Chinese EERFERB policy design are identified.